Women at the center of cowpea value chain development in Nigeria - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
M s. Hadja Salame Shaibu (Fig. 7.1) is a cowpea producer and processor in the Local Government Area of Dawakin Tofa. She grew up in a farming community where crop- livestock integration is a tradition. When she got married few decades ago, Salame continued farming and keeping livestock to support her new family, mainly in sorghum and cowpea production.